(3eHOC GdShGHb GdbVGFjI aj efGRYGJ GdGSJKeGQGJ GdOhdjI (B/s - (3SGeM CMeO eMeO SGdes; (3eMeO QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2025)
(3hjhGLg gPG GdeLGd GdbGfhfj JMOjGJ YOjOI JQJHW HJWhQ hJfhY eUGOQ GdbGfhf GdOhdj ddGSJKeGQ, hJhGab hJfGSb GdbhGYO hGdeHGOF GdbGfhfjI GdeWHbI Ydi gPg GdefGRYGJ hHOhQ hecGfI GdShGHb ef GdCMcGe aj JaSjQ hJWHjb gPg GdbhGYO(B. (3aef LgI, jJSe GdbGfhf GdOhdj ddGSJKeGQ HGdJTJJ hGdJaGhJ Hjf eNJda GdGJaGbjGJ hGdYbhO hGdeeGQSGJ GdOhdjI GdefXeI dg, hef LgI CNQi, jJSe GdJMcje GdOhdj aj efGRYGJ GdGSJKeGQ HGdJYOO hGdJfGaS Hjf eNJda bhGYO eQGcR heDSSGJ hgjFGJ GdJMcje GdeNJUI HgPG GdfhY ef GdefGRYGJ, hgh eG cGf dg ef CKQ aj XghQ eTGcd GdJfGbV hGdJHGjf Hjf GdCMcGe GdJMcjejI GdJj JUOQ ajgG(B.s
This area of law faces numerous challenges, particularly due to the evolving and fragmented nature of the sources of international investment law, the need for consistency and harmonization of the applicable legal norms, and the role and status of precedent in the interpretation and application of such norms. On the one hand, international investment law is marked by its dispersion and variability across treaties, contracts, and international practice. On the other hand, international arbitration in investment disputes is characterized by the multiplicity and competition among various arbitration rules, institutions, and fora, which has led to a proliferation of inconsistent and conflicting arbitral awards
(3CWQhMI (B((3OcJhQGI(B)(3, LGeYI GdbGgQI, cdjI GdMbhb , bSe GdbGfhf GdOhdj (B2025s
(3HHdjhLQGajG(B: (3UaMGJ (B368-399s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdOhdjs; (3GdGSJKeGQ GdCLfHj s; (3GdOhdI GdeVjaIs; (3JYOO GdLfSjI s; (3gjFI GdJMcjes; (3GdJMcje GdOhdjs; (3GdJMcje GdGSJKeGQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs